Relationship Beyond the Task: Leader-Member Exchange and Organizational Citizenship Behavior on Indonesian Generation Z Employees - Endo Wijaya Kartika (Journal of Economics, Business, and Accountancy Ventura, 2025)
The Indonesian hospitality industry must reengage a high-quality workforce composed of Generation Z, recognizing both its strengths and challenges. To achieve this, leaders should adopt a positive approach to fostering high-quality leader-member exchange (LMX) relationships, which can encourage employees to exhibit organizational citi-zenship behavior (OCB). However, there is currently a lack of research specifically examining the relationship between LMX and OCB among Generation Z employees in the Indonesian hospitality sector. This study seeks to address this gap by exploring the application of LMX dimensions and their influence on enhancing OCB within the context of Generation Z employees in the Indonesian hospitality industry. Employing a quantitative causal research design, the study analyzed data from a sample of 300 Generation Z employees working in the sector. The findings reveal that LMX has a positive and significant impact on OCB. Among the LMX dimensions, professional respect emerged as the most influential, followed by affect, contribution, and loyalty. This study highlights the critical role of leaders in recognizing and valuing the profes-sionalism of Generation Z employees as a means to foster positive extra-role behaviors. These findings underscore the importance of leadership strategies that prioritize ap-preciation and respect to enhance employee engagement and performance.